eDify: Enhancing Teaching and Learning Process by Using Video Streaming Server - Hasan, Raza; Palaniappan, Sellappan; Mahmood, Salman; Sarker, Kamal Uddin; Sattar, Mian Usman; Abbas, Ali; Naidu, Vikas Rao; Malali Rajegowda, Puttaswamy (International Journal of Interactive Mobile Technologies (iJIM), 2021)
The study investigates the nature and degree of influence of the range of application usability variables on the learning experience of the students at a specific institution of higher education institution in Oman. The study was carried out via eDify implementation encompassing the usability variables and learning experience of the students. Literature does little to suggest the aforementioned relationship in the context of the Omani higher education. The current study would reveal the variables that are critical to effective technology-based learning of the students. The implications generated through the study would allow the institution involved in the study to effectively implement the variables required for enhanced teaching and learning. The methodology used in the study is divided into an exploratory and the main research. Principal component analysis and a range of regression analyses are conducted to test the relationships between the independent and the dependent variable, “learning experience”. Results suggest that the usability variables have both positive and significant effects on the dependent variable of the learning experience. One usability variable that stands out more than others is the usage of mobile media.